2020
DOI: 10.1037/tra0000868
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists’ vicarious traumatization during the COVID-19 pandemic.

Abstract: During the COVID-19, psychotherapists are often exposed to traumatic material in their sessions, potentially leading to vicarious traumatization. We surveyed 339 therapists about their professional practices and experiences during the pandemic. Results showed that on average therapists experienced moderate levels of vicarious trauma, whereas about 15% experienced high levels of vicarious trauma. A higher level of vicarious trauma was associated with younger age, less clinical experience, and negative online tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 14 publications
3
78
0
Order By: Relevance
“…20 Another multicenter study of 339 psychotherapy HCWs in the United States found 77.6% of them had at least moderate vicarious trauma, with higher trauma scores in younger and early-career therapists. 86…”
Section: Resultsmentioning
confidence: 99%
“…20 Another multicenter study of 339 psychotherapy HCWs in the United States found 77.6% of them had at least moderate vicarious trauma, with higher trauma scores in younger and early-career therapists. 86…”
Section: Resultsmentioning
confidence: 99%
“…The present study demonstrated the impact of COVID-19 in healthcare workers’ psychological well-being and pointed out the key role of defense mechanisms as protective factor against stress and burnout. As the COVID-19 pandemic continues, it is important to prevent and mitigate psychological distress among healthcare professionals [ 68 , 69 , 70 ]. While the global vaccine campaign has begun, the prevention and treatment of psychological distress for frontline workers has not been adequately addressed [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, ME/CFS patients can be traumatized by the physical, psychological, and social impact of the acute emergency period [ 55 , 56 , 57 , 58 , 59 , 60 ]. Second, their friends, family, coworkers, and clinicians can be vicariously traumatized by what is happening [ 8 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Third, these significant others begin to queue up on a continuum that extends from suspicion to support in response to the ME/CFS patient’s observable, decreased participation in activities.…”
Section: Me/cfs Through the Lens Of The Four-phase Modelmentioning
confidence: 99%